THE EFFECT OF PHYSICAL WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON MORALE OF KJKS KOSPIN SYARIAH KARANGANYAR - wulandari, difitri; Sutaryadi, Sutaryadi; Susantiningrum, Susantiningrum (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
The objectives of research are: (1) to find out whether or not there is a significant effect of physical work environment on the morale of KJKS Kospin Syariah Karanganyar employees in 2012, (2) to find out whether or not there is a significant effect of organizational culture on the morale of KJKS Kospin Syariah Karanganyar employees in 2012, and (3) to find out whether or not there is a significant effect of physical work environtment and organizational culture n the morale of KJKS kospin Syariah Karanganyar employees in 2012.This research employed a quantitative research approach with a descriptive method. The population of research was the employees of KJKS Kospin Syariah Karanganyar in 2012. The sampling technique used was saturated sampling technique, the one with all members of population used s the sample so that the number of samples was 42. The technique of collecting data used was questionnaire supported by documentation method. The data analysis use in this research was a multiple linear regression analysis technique. Based on the result of research, it could be concluded that: (1) there was a significant relationship of physical of work environment to the morale of KJKS Kospin Syariah Karanganyar employees in 2012. It could be seen from the values of rstatistic > rtable or 0.450 > 0.304 at significance level of 5%. (2) There was a significant relationship of organizational culture tio the morale of KJKS Kospin Syariah Karanganyar employees in 2012. It could be seen from the values of rstatistic > rtable or 0.458 > 0.304 at significance level of 5%. (3) There is a significant relationship of physical work environment and organizational culture to the morale of KJKS Kospin Syariah Karanganyar employees in 2012 . It could be seen from the values of Fstatistic > Ftable or 11.165 > 3.238 at significance level of 5%. With the result of multiple linear equation of ? = 7.779 + 0.526X1 + 0.315X2. The physical work environment variable give relative contribution of 48.93% and effective contribution of 17.82%.Organizational culture variable give relative contribution of 51.07 and effective contribution of 18.59%. Keywords: physical work environment, organizational culture, and morale.